Investigation of the variability of local ice strength by exposure to the spectrum of infrared radiation of various lengths - Lysyy, Andrey; Ivanov, Oleksander; Kotenko, Vitaliy (Technology audit and production reserves, 2019)
The object of research is the interaction of the infrared radiation spectrum with ice. The work is aimed at determining this interaction in order to ensure the safe passage of the route by ice-class vessels independently or as part of a caravan during the winter navigation period, in the freezing waters of non-Arctic seas and rivers, as planned and without delays. To solve this problem, in the course of the study, similarity coefficients equal to those calculated were used, and temperature intervals were determined corresponding to the selected discrete intervals of ice thickness. The processing of laboratory test data was reduced to statistical analysis, the purpose of which was to determine the statistical characteristics of the studied quantities. As well as the establishment of correlation between the studied values and the assessment of the strength characteristics of low-supply ice. This is due to the aim of establishing regressive relationships between the strength limits of ice and its temperature, salinity, and density. To solve a similar problem, various scientific groups conducted field studies and tests with the Dikson icebreaker (Russia) for cutting ice with a jet of temperature-activated water or laser radiation with a power of 30 to 200 kW, which is transmitted via an optical fiber cable. Compared with the considered methods, which have disadvantages in the following: – mobility of devices; – weight of devices; – uninterrupted supply of the emitter with a sufficiently large power for an indefinite time; – formation of boiling water, which is formed during laser cutting of ice, which, in turn, at negative outside air temperatures, leads to a rapid coalescence of the section, which becomes much stronger; – laser-cut pieces of ice within the channel will go under the vessel. In the presence of shallow depths, this may stop the movement of the vessel or create a risk of damage to the hull. Thanks to the research results, it is possible to create an experimental self-propelled automated installation for the destruction of ice in freezing waters and on approach channels to the port, which allows: – soften the ice at the first stage of work; – at the second – cut it; – at the third – turn it into water.